2003
DOI: 10.1007/s00586-002-0495-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngolaryngeal lesions in patients undergoing cervical spine surgery through the anterior approach: contribution of methylprednisolone

Abstract: IntroductionProlonged intubation is associated with various ear, nose, and throat (ENT) complications, notably paresis or paralysis of the vocal cords [13,14]. Such complications may arise even after intubation of short duration [3,4,7] and regardless of the type of surgery. In reports of cervical spine surgery through the anterior approach, these complications have been noted and attributed to the surgical maneuvers as well as to intubation [1,2,10,11,12]. Moreover, these procedures may lead to other complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 8 publications
0
47
0
Order By: Relevance
“…The authors found a risk of vocal cord paralysis of 2.6% in the steroid group, compared to 3.8% in the control (not statistically significant). 16 …”
Section: Discussionmentioning
confidence: 99%
“…The authors found a risk of vocal cord paralysis of 2.6% in the steroid group, compared to 3.8% in the control (not statistically significant). 16 …”
Section: Discussionmentioning
confidence: 99%
“…Anterior plating contributes to an immediate stabilization that enables osseous fusion and the latter avoids prolonged neck brace use, allowing for early cervical mobilization and a shorter hospitalization. [1][2][3][4][5][6][7][8][9][10] Despite its widespread use and the relative simplicity of the technique, the risk of potential complications still ranges from 5% to 35%. [1][2][3]8 Some complications have a low risk, such as pharyngoesophageal edema, small hematoma, infection, or transitory recurrent laryngeal or hypoglossal nerve lesions, whereas others are life-threatening, such as epidural abscess, mediastinitis, or edema and hemorrhage with upper airway involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cervical fixation through different devices has been used for multiple pathologies, such as traumatism, compressive myelopathy, or spinal infections since 1967. [1][2][3][4][5][6][7][8][9] It is a broadly developed technique in neurosurgery with a reported complication rate of 5%-35%. 1 Clinical evolution is usually satisfactory and well tolerated, although serious complications can occur, such as mediastinitis, severe hemorrhage, or epidural abscess.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotics are typically used following spinal surgery to prevent or treat infections at the surgical site. As these complications can impair swallowing function, and lead to secondary restrictions of pharyngeal movement or epiglottic deflection, the use of steroid treatment or antibiotics post-operatively has potential to improve swallowing outcomes [23, 24]. In the studies reviewed, steroids and antibiotics appeared to contribute to improved swallowing function when used in addition to other swallowing interventions, primarily tube feedings [12, 13].…”
Section: Discussionmentioning
confidence: 99%